Optimization of Lightly Calcined MgO Fluidized-Bed Roaster Jet Feed Structure Parameters - Xue-yi Ma; Ze Gong; De-xi Wang; Hui Dong; Bo Liu; Hong-lei Yu; Xiao Hong; Teng Ren (Journal of Chemical Engineering of Japan, 2023)
This work aims to improve the material segregation, bottom-of-furnace aggregation, and uneven particle distribution in the feeding area of a lightly calcined MgO airflow hearth roaster. A feeding structure type based on the jet is proposed, and a large cold experimental device with an 85 mm inner diameter and 3500 mm height is established based on the jet. Then the effects of different parameters on the flow characteristics of magnesite particles in the jet-feeding device of the lightly calcined MgO furnace are investigated. The experimental results indicate that the feeding structure based on the jet could not only improve the fluidization gas velocity and material segregation in the feeding area but also completely solve the bottom of furnace aggregation, enhancing the gas–solid mixing efficiency and improving the particle distribution uniformity. The optimized key structural parameters reveal that the best scheme for the jet feeding device is as follows: the nozzle distance is 225 mm, the nozzle diameter is 16 mm, and the length–diameter ratio is <2.